Enhancing inventory models using fuzzy extended principles for optimization - Ankit Dubey; Ranjan Kumar (Journal of Fuzzy Extension and Applications)
In this work, the authors have considered a physical world concern related to an inventory model under a Neutrosophic environment. We aim to perceive the ideal Total Cost (TC) for the proposed Inventory Management (IM) model without considering the shortage. To achieve this aim, we use trapezoidal Neutrosophic environments. For that purpose, we consider an example to clarify the results of the given model and present computational results. The purpose of the suggested method is to not only solve contemporary numerical problems but also handle new sorts of problems. Finally, we conclude our research by providing graphical, logical, and tabular evaluations with the prevailing methodologies.